Estimation of P-wave velocities for unsaturated geo-materials - Leong, Eng Choon (2013)
Using P-wave velocity as a proxy for degree of saturation is useful in many applications. The effect of saturation on P-wave velocity of geo-materials has been frequently modeled using Biot-Gassmann equation. However Biot-Gassmann equation is not able to fully account for the effect of partial saturation. In this study, the effects of degree of saturation on P-wave velocity of rocks are investigated. Modifications to the Biot-Gassmann equation are then suggested to improve the estimation of P-wave velocities for unsaturated rocks. The modifications are evaluated with several data sets and were found to provide an improved estimate of P-wave velocity for unsaturated rocks to within ±10%.